2019
DOI: 10.1177/0011000019886972
|View full text |Cite
|
Sign up to set email alerts
|

“Sincerely Held Principles” or Prejudice? The Tennessee Counseling Discrimination Law

Abstract: In 2016, Tennessee became the first state to allow counselors and therapists in private practice to deny services to any client based on the therapist’s sincerely held principles. The law’s proponents framed mental health care ethics as infringing on counselors’ religious liberties; its critics denounced the bill because it apparently targeted LGBT+ individuals. This exploratory study is the first statewide assessment of LGBT+ Tennesseans’ ( N = 346) perceptions of the law and how it may affect their help-seek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…A growing body of research has found that anti-LGBT legislation is related to psychological distress for LGBTQ people and their family members during anti-LGBTQ initiatives (e.g., Arm et al, 2009; Frost & Fingerhut, 2016; Grzanka et al, 2020; Horne et al, 2011; Levitt et al, 2009; Lin et al, 2019; Rostosky et al, 2009; Riggle et al, 2010; Russell, 2007; Russell & Richards, 2003), and that the trauma-related effects of these campaigns are reported to be long-lasting (Russell et al, 2011). Living in states without LGB protections, or with an explicit denial of services to LGB people, is related to increased mental health concerns among LGB people when compared with LGB people living in jurisdictions with sexual orientation protections (Hatzenbuehler et al, 2010; Lin et al, 2019; Raifman et al, 2018; Tatum, 2017).…”
Section: Structural Stigma and Anti-lgbtq Legislationmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of research has found that anti-LGBT legislation is related to psychological distress for LGBTQ people and their family members during anti-LGBTQ initiatives (e.g., Arm et al, 2009; Frost & Fingerhut, 2016; Grzanka et al, 2020; Horne et al, 2011; Levitt et al, 2009; Lin et al, 2019; Rostosky et al, 2009; Riggle et al, 2010; Russell, 2007; Russell & Richards, 2003), and that the trauma-related effects of these campaigns are reported to be long-lasting (Russell et al, 2011). Living in states without LGB protections, or with an explicit denial of services to LGB people, is related to increased mental health concerns among LGB people when compared with LGB people living in jurisdictions with sexual orientation protections (Hatzenbuehler et al, 2010; Lin et al, 2019; Raifman et al, 2018; Tatum, 2017).…”
Section: Structural Stigma and Anti-lgbtq Legislationmentioning
confidence: 99%
“…Depressive symptomatology and anxiety are commonly reported by LGBTQ people in relation to minority stress indices, such as internalized stigma, and gender-related victimization and discrimination (e.g., Sarno et al, 2020; Testa et al, 2015; Timmins et al, 2017). Moreover, these constructs have been utilized in studies assessing minority stress and structural stigma in relation to anti-LGBT initiatives (Grzanka et al, 2020; Horne et al, 2011; Rostosky et al, 2009 , 2010; Russell, 2007), and in assessing gender-related discrimination and coping strategies of TNG individuals (Budge et al, 2013; Lloyd et al, 2019). Exploring depressive symptomatology and anxiety may shed light on how LGBTQ individuals respond to policy-related structural stigma, which may inform interventions and coping strategies.…”
Section: Structural Stigma and Anti-lgbtq Legislationmentioning
confidence: 99%
“…Discriminatory political efforts aimed at LGBTQ people are an example of structural stigma, which is the combination of sociocultural conditions, social norms, and institutional policies that impose restrictions on access to resources and opportunities afforded to stigmatized individuals, impacting their well-being (Hatzenbuehler, 2016). During anti-LGBTQ political campaigns, a growing body of research has documented the harmful mental health impact of structural forms of stigma for sexual and gender minorities and their families, including anxiety, stress, and depression (Hatzenbuehler et al, 2010: Horne, McGinley, et al 2020; Levitt et al, 2009; Rostosky et al, 2009), sadness, alienation, and anger (Russell, 2000; Russell & Richards, 2003), help-seeking attitudes and behaviors (Grzanka et al, 2020), suicidal ideation, and substance abuse (Hatzenbuehler et al, 2010), couples’ psychological distress (Frost & Fingerhut, 2016) and worry and anxiety of family members of LGBTQ people (Horne et al, 2011). During Taiwan’s recent adoption of marriage equality, it was found that those who reported greater exposure to anti-LGBT messages reported greater suicidal ideation and poorer mental health (Huang et al, 2020; Lin et al, 2019).…”
Section: Virtue Is Not Solitary: It Is Bound To Have Neighborsmentioning
confidence: 99%
“…Psychologists have documented how, even though conscience clauses tend not to specify a client population, the values conflicts behind them are typically motivated by religiously conservative individuals seeking the option to not serve SGM clients (Mintz et al, 2009). High-profile public debate about the Tennessee legislation focused on how what came to be known as the “Counseling Discrimination Law” (Grzanka, Spengler, Miles, Frantell, & DeVore, in press) targeted SGM individuals, even though the law’s architects refused to acknowledge any discriminatory intent or include language in the bill that specified which kinds of clients might cause a therapist to deny services (Plazas, 2016). Furthermore, because the Tennessee law is one of the first statewide conscience clauses for licensed mental health care providers (Green, 2016), little is known about how such policies might affect the help-seeking practices of its imagined targets (i.e., SGM people) and/or how such laws affect SGM individuals’ perceptions of mental health care and therapists.…”
mentioning
confidence: 99%